Medal Books and Emblem Books: A Face-to-Face Encounter between two Original Creations from the Humanistic World - Rodríguez Bote, María Teresa (Eikón / Imago, 2026)
This paper aims to establish a connection between the genres of medal books, as visual and iconographic sources, and their parallels and divergences in relation to emblem books, both phenomena within the Renaissance. While both textual and visual genres have been widely and independently studied, never have they been drawn as close manifestations and put into comparison. Similarities include formal elements, as well as their educational purpose, their admiration for Antiquity and the use of mythological characters. Nevertheless, medal books focus on the life of exemplary historical or mythological figures, with illustrations imitating ancient coins, whereas emblems allow for greater thematic breadth and graphic creativity. On the other hand, a chronological comparison between both is explained; it is thus noted that interest in medals began in the 15th century, as its key publication, the Illustrium imagines by Andrea Fulvio, was published at an early date, in 1517. This period slaps over time with the so-called “pre-emblematic” or “proto-emblematic” phase. During the first half of the 16th century, Medallistics was at its height and so precedes Alciato’s volume (1531); however, Emblematica ends up imposing its design and layout over medal books.